Peran Brand Experience terhadap Behavioral Loyalty pada Pengguna Smartphone di Indonesia - Sandi Setiawan; Unggul Kustiawan (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
This research investigates the importance of Brand Experience in fostering Behavioral Loyalty among smartphone users in Tangerang Regency, with Brand Love, Brand Trust, and Brand Satisfaction with the mediating roles of Brand Love, Brand Trust, and Brand Satisfaction.          A quantitative approach was employed using the Covariance-Based Structural Equation Model (CB-SEM). Data were collected through an online questionnaire distributed via Google Form to members of Generation Z and Millennials residing in Tangerang Regency, who have a stable income and have independently purchased smartphones. A total of 212 valid responses were obtained. Data analysis was conducted using SmartPLS 4.0 software. The results indicate that Brand Experience has a positive influence on Brand Love, Brand Trust, and Brand Satisfaction. Furthermore, these three mediating variables also significantly affect Behavioral Loyalty. The findings highlight the importance of managing consistent and satisfying brand experiences to foster emotional attachment, trust, and customer satisfaction. These elements are crucial in building long-term behavioral loyalty toward smartphone brands. Practically, companies are encouraged to enhance emotional engagement, build customer trust, and ensure satisfaction to maintain a loyal consumer base in the highly competitive smartphone market.